Communication with Tabayyun on Negative Issues of Presidential Candidates on Social Media - Firmansyah; Kurnia, Septiawan Santana; Wiksana, Wiki Angga; Fadhli, Ahmad; Azzahra, Sharla; Cahyaning, Ranisa (Mediator: Jurnal Komunikasi, 2025)
The comment section feature on social media serves as a public space for discussion, especially on news accounts. However, discussions often become a means of spreading hate speech and even hoaxes. The concept of tabayyun, as an approach rooted in verification and the search for truth, is very important in encouraging responsible discussion. This study aims to identify communication patterns that may spread misinformation and how this can be addressed through the application of tabayyun. A qualitative methodology was employed using a netnographic approach, with data collected through online data capture techniques from January 2023 to February 2024, comprising 923 posts. The analysed data was then used to draw conclusions that could serve as guidelines for developing tabayyun communication strategies in managing the overwhelming flow of information. Findings indicate that on the accounts of @pikiranrakyat and @republikaonline, the balance between positive and negative news coverage regarding the three candidate pairs is relatively balanced. Negative news, tends to generate a significant number of comments, creating space for active discussion among netizens, with comments that indicate hate speech. In Islam, the tabayyun communication pattern can create social responsibility to clarify and verify the information presented, whether by administrators or other netizens.